Impacts of guidelines transition on greenhouse gas inventory in the livestock sector: a study case of Korea - Eska Nugrahaeningtyas; Jong-Sik Lee; Dong-Jun Lee; Jung-Kon Kim; Kyu-Hyun Park (Journal of Animal Science and Technology)
The Paris Agreement signatories have committed to limit global average temperature increase above pre-industrial levels to below 2°C. Reporting of the greenhouse gas (GHG) inventory is regulated by the United Nations Framework Convention on Climate Change. Currently, countries are transitioning from the Measurement, Reporting, and Verification reporting system to the Enhanced Transparency Framework (ETF) reporting system. Under the ETF, countries are required to use the 2006 guidelines (GL). This study explored how replacing the 1996 GL with the 2006 GL or the 2019 Refinement impacts the overall GHG inventory from the livestock sector, with Korea as a case study. The result affirmed that changes in guideline led to changes in total estimated emissions. Moving from the 1996 GL to the 2019 Refinement resulted in more significant differences in estimated emissions than moving to the 2006 GL in terms of source-based emissions, annual inventory, or trend. Notably, guidelines’ changes also impacted the proportion of each source’s contribution to total estimated emissions. While applying the most recent guidelines is expected to produce more accurate estimations, consistency with the previous inventory calculated with previously used guidelines should be maintained. Additionally, the changes in the contribution of each source clarifies that although enteric fermentation is the largest contributor of GHGs, relevant mitigations are likely less feasible compared to those related to manure management. This is because of naturally occurring biological processes. Thus, mitigations in manure management are suggested.